'My people perish for lack of knowledge': barriers and facilitators to integrated HIV and hypertension screening at the Kenyatta National Hospital, Nairobi, Kenya. Issue 1 (27th January 2023) - Wamuti, Beatrice; Owuor, Mercy; Magambo, Christine; Ndegwa, Margaret; Sambai, Betsy; Temu, Tecla M; Farquhar, Carey; Bukusi, David
Abstract : Introduction: HIV and cardiovascular disease (CVD) are the two main causes of death in Kenya with hypertension as CVD's leading risk factor and HIV infection a risk factor for hypertension. We qualitatively evaluated the feasibility of integrated HIV and hypertension screening at Kenyatta National Hospital. Methods: We conducted two focus group discussions (FGDs) in November 2020 (female FGD: n=7; male FGD: n=8) to elicit facilitators, barriers and viability of integrated diagnosis and management of both conditions at HIV testing service (HTS) facilities. Participants were selected using convenience sampling and were not pair matched. All participants had received HTS. All female clients had confirmed hypertension, while male relatives had been contacted for HIV and hypertension screening through a modified assisted partner services model—where a trained healthcare provider supports notification. Transcripts were coded independently, and the codebook was developed and revised through consensus discussion. Data were analysed using thematic content analysis. Results: Main barriers to diagnosis and management included limited public awareness of hypertension risk factors and on improved treatment outcomes for those on lifelong HIV treatment, high cost of hypertension care despite free HIV care and healthcare system challenges especially medication stockouts. Strong support systems at family and healthcare levels facilitated care and treatment for both conditions. Participants recommended improved public awareness through individual-level communication and mass media campaigns, decentralised screening services for both HIV and hypertension, and either free or subsidised hypertension care services delivered alongside HIV treatment services. Most felt that an integrated HIV and hypertension service model was viable and would improve healthcare outcomes. Conclusion: Patient-centred care models combining HIV and hypertension services hold promise for integrated service delivery.